HUBUNGAN KONSEP DIRI DAN METAKOGNITIF DENGAN PRESTASI BELAJAR DI AKBID UMMI KHASANAH - Ardhianingtyas, Nisa; Susilo, Hayun Manudyaning (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
Correlation of The Self-Concept and The Metakognition To Their Learning Achievement of Akbid Ummi Khasanah. Humans as organisms have the motivation to develop. The developments helped establish the views and feelings of the ability to achieve learning success. This research objective is: 1) To determine the correlation of the self-concept to learning achievement, 2) to determine the correlation of the metakognition to learning achievement, 3) to determine the correlation of the self-concept and the metakognition to learning achievement. The research type was an observational analytic with cross sectional approach. The research population was a students majoring in the Diploma III Program in Obstetrics of Akbid Ummi Khasanah of Bantul Yogyakarta and study sample were students of semester II. With the data collection techniques was using questionnaire and the result of Obstetrics Care I midterm test. Data analyzing was using the Kendall Tau and Logistic Regression Ordinal. The result of the research is there is a significant correlation of the self-concept to learning achievement, the value of sig. (2-tailed)<0.05 is 0.000<0.05. There is a significant correlation of the metakognition to learning achievement, the value of sig. (2-tailed)<0.05 is 0.000<0.05. There is a significant and positive correlation of the self-concept and metakognition to learning achievement, the value of sig. <0.05 and the estimate is positive. Keywords : self-concept, metakognition, learning achievement